Saturday

April 19, 2014

April 19, 2014

Posted by **shirley** on Saturday, August 27, 2011 at 5:49pm.

- algebra -
**Damon**, Saturday, August 27, 2011 at 7:13pm2 x^2 - 3 x - 2 = 0

x = [ 3 +/- sqrt (9 + 16) ]/ 4

x = [ 3 +/- sqrt(25) ]/ 4

= [3+5]/4

or

= [3-5]/4

= 2 or -1/2

check:

------------

(x-2)(2x + 1) = 2 x^2 -3x - 2 yes

**Related Questions**

algebra - What is the value of the expression 2x to the 2nd power + 3xy -4y to ...

Algebra - Factor each of following expressions x (4th power) - x (3rd power) - ...

advanced math - Hi, I am trying to solve graphing quadratic equations. One of ...

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

Intermediate Algebra - for the polynomial function h(x)=2x to the 4th power-x to...

Algebra - Simplify the following [2x / (3x (2nd power) - 5x - 2] + [(x-1) / (x (...

elemmanarty algebra - Divide xy to 3rd power -3xy to 2nd power +2x to 2nd power ...

Algebra - Solve the following 2x (2nd power) + 5x - 12 = 0

algebra - solve for x (24+2x)(10+2x) - 240 = 152 First multiply. 24(10) = ___ 2x...

algebra - how do I evaluate 2x to the 4th power + 2 x to the 3rd power + x to ...